Nilai Tanda dan Nilai Simbol Pada E-Commerce Shopee: Perilaku Konsumsi Mahasiswa FISIP ULM - Meiliolibta Utopia; Khairussalam (Huma: Jurnal Sosiologi, 2023)
The era of globalization, which has increased the level of technological development, has had an impact on the consumption patterns of FISIP ULM students due to the emergence of the e-commerce application, Shopee. This study aims to find out the symbolic value that exists in e-commerce Shopee so that it raises consumption behavior in FISIP ULM students. This type of research uses qualitative research methods with a descriptive approach which will be formulated using the theories of postmodern society, consumer society and hyperreality from Jean Baudrillard. The time of the research was carried out for 3 months with data collection and data analysis carried out. Data collection techniques were carried out by observation, interviews, and also literature studies. The data analysis technique uses the Miles and Huberman interactive model with the following stages: 1) data reduction, 2) data presentation, and 3) drawing conclusions. The results of this study show that the value of the signs and symbols on Shopee greatly influences student shopping interest. Free shipping vouchers are the most popular because they can reduce shipping costs. Apart from that, the large amount of cashback and other facilities, such as: ShopeeFood, ShopeePay, ShopeePay Later, to Shopee Games makes shopee users, especially FISIP ULM students, even more tempted to shop as they wish with this e-commerce shopee. The advice for FISIP ULM students is not to be tempted by symbolic value by always prioritizing needs over wants, being careful and reconfirming the items purchased from the seller.